Предмет: Алгебра, автор: KseniyaShulga

√(10)+√(6) √(10)-√(6)  
√(10)+√(6)    √(10)+√(6) 
  
помогите упростить

Ответы

Автор ответа: hasulisa
0
  frac{ sqrt{10}+ sqrt{6}  }{sqrt{10}+ sqrt{6}}- frac{sqrt{10}- sqrt{6}}{sqrt{10}+ sqrt{6}} = frac{sqrt{10}+ sqrt{6}-sqrt{10}+ sqrt{6}}{sqrt{10}+ sqrt{6}}=

frac{2sqrt{6}}{sqrt{10}+ sqrt{6} }=  frac{2 sqrt{6}*( {sqrt{10}- sqrt{6})}}{10-6 }}= frac{2 sqrt{60}-2*6}{4} = frac{4( sqrt{15}-3) }{4} = sqrt{15} -3
Похожие вопросы
Предмет: Алгебра, автор: Айсылу16